ВЫСОКОЧУВСТВИТЕЛЬНОЕ ВИДЕОЭНДОСКОПИРОВАНИЕ ПОВЕРХНОСТЕЙ ГЕОМЕТРИЧЕСКИХ ТЕЛ - A. P. Markov; S. S. Sergeyev; A. G. Starovoytov; E. I. Marukovich; E. M. Patuk (Литьë и металлургия)
Waysandmeansofhighlysensitivedefectoscopyareconsidered.